A novel mutation in the RSPO4 gene in a patient with autosomal recessive anonychia. (1st April 2017) - Khalil, S.; Hayashi, R.; Daou, L.; Staiteieh, S. A.; Abbas, O.; Bergqvist, C.; Nemer, G.; Shimomura, Y.; Kurban, M.
Summary: The Wnt signalling pathway is a major pathway involved in the embryogenic development of the various organs of the body. Appropriate signalling in this pathway relies on the proper functioning of several proteins including the R‐spondin family of proteins. Deactivating mutations in R‐spondin 4 are associated with anonychia. We present the case of a 26‐year‐old man presenting with anonychia of the 20 nails, which had been present since birth. Using genetic studies, we identified a novel nonsense mutation, c.164‐165TC>AA, characterized by two consecutive mismatch bases. To our knowledge, this mutation is the first to be reported in R‐spondin 4 in a Lebanese population. Evaluating new patients with anonychia provides fruitful clinical and molecular findings. Abstract : Click here for the corresponding questions to this CME article.